REFORMS IN THE ITALIAN HIGHER EDUCATION SYSTEM (Education in the 21st Century, 2023)
Italy is one of the developed countries of Europe. And, being a co-founder of the Bologna Process, Italy implemented the reforms outlined in the Bologna Declaration in order to integrate into the European educational area, while preserving its national identity.This article examines the reforms that have taken place in the Italian higher education system under the Bologna Process.